The pathogenesis of influenza in intact alveoli: virion endocytosis and its effects on the lung’s air-blood barrier - Hook, Jaime L.; Bhattacharya, Jahar (Frontiers in Immunology, 2024)
Lung infection by influenza A virus (IAV) is a major cause of global mortality from lung injury, a disease defined by widespread dysfunction of the lung's air-blood barrier. Endocytosis of IAV virions by the alveolar epithelium -the cells that determine barrier function -is central to barrier loss mechanisms. Here, we address the current understanding of the mechanistic steps that lead to endocytosis in the alveolar epithelium, with an eye to how the unique structure of lung alveoli shapes endocytic mechanisms. We highlight where future studies of alveolar interactions with IAV virions may lead to new therapeutic approaches for IAV-induced lung injury.